Ablation of typical atrial flutter using the novel MediGuide 3D catheter tracking system: a review of the literature. (July 2014) - Muser, Daniele; Magnani, Silvia; Santangeli, Pasquale
<x xml:space="preserve">Abstract</x> The MediGuide™ system is a novel technology for non-fluoroscopic 3D catheter tracking during cardiovascular electrophysiological procedures. The system allows for precise catheter visualization on pre-recorded conventional fluoroscopy images, with significant reduction of fluoroscopy exposure. This might translate into improved safety for both patients and operators, without affecting the procedural efficacy. Preliminary data suggest that the MediGuide technology is at least as safe and effective as conventional systems for mapping and catheter ablation of a variety of supraventricular arrhythmias, with a significantly reduced fluoroscopy exposure. In this review, the authors summarize data from the available literature data on catheter ablation of typical atrial flutter using the novel MediGuide technology.